Nutrition Education Video Can Improve Knowledge And Hemoglobin Levels In Students Of Sman 1 Singaraja Bali Province - Ida Ayu Eka Padmiari; Desak Made Ardhya Pramesti Suci Sanjiwani; Desak Putu Sukraniti (CV. AFDIFAL MAJU BERKAH, 2025)
Based on the 2013 and 2018 Riskesdas, the prevalence of anemia in adolescents in Indonesia has increased from 18,4% to 32%. And there are 21,4% of young women forget to take iron tablets. The purpose of this study was to determine differences in knowledge and hemoglobin levels before and after giving nutrition education videos to female students of SMAN 1 Singaraja. The type of research used is quantitative research with a quasi-experimental design using the one-group pretest-posttest design method. The number of samples in this study were 61 female students. Using a nonparametric test, namely the Wilcoxon Test. The characteristics of the sample were 32 samples (51,6%) aged 16-20 years, while 30 samples (48,4%) aged 10-15 years. The results of data collection show that the average age of the sample is 16 years, where the average sample has a BMI of 20,18 kg/m2 which is a normal nutritional status. There was an increase in the average value of the sample's Hb level of 0,3 from 14,2 to 14,5. The knowledge of the sample experienced an increase in the average value of 6,7 from 71,2 to 77,9. Wilcoxon Test Results On the Hb level variable, the sig. 0,159 (sig. >α ; α = 0,05) so that there is no significant difference in the results of Hb levels between before and after the nutrition education intervention is given.In the knowledge variable, the sig value is obtained. 0,000 (sig. <α ; α = 0,05), where there is a difference in the results of knowledge between before and after the nutrition education intervention is given. Therefore nutrition education is needed in any media to maintain health and prevent anemia in female students